2022
DOI: 10.1111/jocd.15121
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between seborrheic dermatitis and metabolic syndrome parameters

Abstract: Seborrheic dermatitis (SD) is a chronic superficial disease that is more common in 3%-5% of the population (2.35%-11.3%) especially in men. It is frequently involved in skin folds such as the scalp, eyebrows, eyelids, nasolabial region, ear, sternal region, axilla, under the breasts, navel, and inguinal region. It is common in the infantile and adolescence period, increases after the age of 50. 1,2 The most accused in its etiopathogenesis can be listed as seborrhea, microbial factors such as malassezia, candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 32 publications
(98 reference statements)
0
23
0
3
Order By: Relevance
“…Previous evidence showed a lower level of HDL in people with SED compared to those without this condition 55 . Further, a recent cross‐sectional study illustrated that the prevalence of MetS was substantially higher in patients with SED than in the control group ( p = 0.004) 56 . Furthermore, the number of people with elevated TG levels in the SED group was significantly greater than in the control group ( p = 0.015).…”
Section: Discussionmentioning
confidence: 92%
“…Previous evidence showed a lower level of HDL in people with SED compared to those without this condition 55 . Further, a recent cross‐sectional study illustrated that the prevalence of MetS was substantially higher in patients with SED than in the control group ( p = 0.004) 56 . Furthermore, the number of people with elevated TG levels in the SED group was significantly greater than in the control group ( p = 0.015).…”
Section: Discussionmentioning
confidence: 92%
“…Considering blood lipids, Akbas et al reported that patients with SD tend to have significantly higher total cholesterol concentration and LDL along with lower HDL [ 60 ]. The same authors suggested that the presence of MS, particularly dyslipidemia, may increase the risk of SD appearance and its severity [ 60 ].…”
Section: Seborrhoeic Dermatitismentioning
confidence: 99%
“…Considering blood lipids, Akbas et al reported that patients with SD tend to have significantly higher total cholesterol concentration and LDL along with lower HDL [ 60 ]. The same authors suggested that the presence of MS, particularly dyslipidemia, may increase the risk of SD appearance and its severity [ 60 ]. They suggested that involvement of particular sites with SD lesions may be more predictive of MS, especially the scalp, eyebrows, and nasolabial folds [ 60 ].…”
Section: Seborrhoeic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Overweight, short stature is one of the main risk factors for the development of this disease in different ethno-territorial groups. The pathogenetic link between abdominal obesity and SD is quite clear: the severity of skin manifestations in overweight patients is registered much more often than in normal weight patients [3]. Previous studies have examined individual predictors of clinical prognosis in patients with SD, and there are virtually no studies that would conduct a comprehensive analysis of clinical and anthropometric predictors, which would objectify the long-term prognosis for this category of patients.…”
Section: Introductionmentioning
confidence: 99%